Influence of mould-active antifungal treatment on the performance of the Aspergillus-specific bronchoalveolar lavage fluid lateral-flow device test - Eigl, Susanne; Reinwald, Mark; Spiess, Birgit; Buchheidt, Dieter (International journal of antimicrobial agents, 2015)
The effect of mould-active antifungal (AF) therapy/prophylaxis on the performance of the Aspergillus-specific lateral-flow device (LFD) test for diagnosing invasive pulmonary aspergillosis (IPA) was evaluated. This was a retrospective analysis of patients diagnosed with probable or proven IPA (according to revised EORTC/MSG criteria) at the Medical University of Graz (Austria) and the University Hospital of Mannheim (Germany) between February 2011 and December 2014. In total, 60 patients with 63 bronchoalveolar lavage fluid (BALF) samples were included in the analysis. Patient charts were reviewed regarding AF treatment at the time of bronchoscopy, and the influence of AFs on the performance of the LFD and BALF galactomannan (GM) ELISA results was calculated. Overall, 54 patients (57 BALF samples) had probable IPA and 6 patients (6 samples) had proven IPA. In 21/63 samples (33%) (from 19 patients), systemic mould-active AFs had been initiated before bronchoscopy. Of 63 BALF samples, 16 (25%) yielded a false-negative LFD result. The sensitivity of the LFD for probable/proven IPA was significantly lower in those receiving mould-active AFs compared with those without (52% vs. 86%; P=0.006). Similar results were found for BALF GM, with sensitivities decreasing under systemic AFs (71% vs. 95%, P=0.013 with the 0.5 ODI cut-off; 52% vs. 81%, P=0.036 with the 1.0 cut-off). These results suggest that the sensitivity of the BALF LFD and BALF GM assays may be reduced in the presence of mould-active AF treatment. Negative results in patients on AFs should therefore be interpreted with caution.